Conceptual fluency increases recollection: behavioral and electrophysiological evidence - Wang, Wei; Li, Bingbing; Gao, Chuanji; Xu, Huifang; Guo, Chunyan (Frontiers in Human Neuroscience, 2015)
It is widely established that fluency can contribute to recognition memory. Previous studies have found that enhanced fluency increases familiarity, but not recollection. The present study was motivated by a previous finding that conceptual priming affected recollection. We used event-related potentials to investigate the electrophysiological correlates of these effects with conceptually related two-character Chinese words. We found that previous conceptual priming effects on conceptual fluency only increased the incidence of recollection responses. We also found that enhanced conceptual fluency was associated with N400 attenuation, which was also correlated with the behavioral indicator of recollection. These results suggest that the N400 effect might be related to the impact of conceptual fluency on recollection recognition. These study findings provide further evidence for the relationship between fluency and recollection.